A retrospective study of clinical and epidemiological characteristics of snakebite in Napo Province, Ecuadorian Amazon - Patiño, Ricardo (2023)
BACKGROUND: Snakebite envenoming remains a relevant public health problem in tropical and subtropical countries. In Ecuador, this is particularly true in an area of great diversity like the Amazon region. Nevertheless, there is scarce information about epidemiological and clinical characteristics of these accidents in this area. METHODS: This was a descriptive and retrospective study of snakebite cases treated at a tertiary hospital in the Napo Province, Ecuadorian Amazon, from 2015 to 2019. We collected sociodemographic and snakebite-related information, clinical aspects and the use of antivenom and antibiotics from medical records. RESULTS: Information from 133 snakebite accidents was reviewed in this time period. Reports of snakebite envenoming decreased over the years. In total, 67% of those bitten were from nearby indigenous communities, which were the most affected groups. When a species was identified, Bothrops atrox was responsible for the highest number of cases registered. Local clinical manifestations were more frequent than systemic signs, in keeping with the typical effects produced by bothropic venoms. Additionally, data showed that more antivenom vials were given than those suggested by the protocol of the Ecuadorian Ministry of Health, in proportion to the grade of severity. Finally, we identified a low incidence of adverse reactions with antivenom administration, as well as a frequent use of antibiotics. CONCLUSIONS: The profile of snakebite accidents in the Napo Province is very similar to that described for other localities in the Amazon region of Ecuador and neighboring countries, with its challenges and limitations. Such aspects underlie the importance of establishing a robust and science-based public health program to respond to this frequent, but neglected, tropical disease.